(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purposes of this dissertation were 1) to study the components of Buddhist attribute administrators in disruptive innovation society for educational institutes, 2) to develop a causal model for Buddhist attribute administrators in disruptive innovation society for educational institutes, and 3) to propose the causal model for Buddhist attribute administrators in disruptive innovation society for educational institutes. Multiphase mixed methods research was designed by using quantitative methods to extend qualitative results. It was divided into 3 phases. Phase 1 qualitative research, the key informant was qualified person in education administration and were selected by purposive sampling of 12 key informants.Research tool was interview form and data was analyzed by using analytic induction. Phase 2 was a qualitative research, focus group discussion by experts who were academics in the field of Buddhist Education Administration, and qualified person in education administration using purposive sampling of 9 experts, data were analyzed by content analysis. Phase 3 was quantitative research by using a questionnaire to validate the causal model for Buddhist attribute administrators in disruptive innovation society for educational institutes. The sample group was determined by using a sample size of 10 samples per 1 number of path showing the relationship between the variables in the model of all 43 paths. Therefore, the appropriate sample size should be 450 samples. Data were analyzed by using descriptive statistics, Pearson’s Correlation Coefficient and analyzed to validate the model with the empirical data, and analyze the direct and indirect effects with the LISREL program. Results were shown as follows: 1. The components of Buddhist attribute administrators in disruptive innovation society for educational institutes consisted of 4 factors: 1) attribute administrators in disruptive society, 2) attribute administrators in disruptive innovation, 3) Buddhist attribute administrators, 4) Buddhist attribute administrators in disruptive innovation society. Therefore, there will initiate Buddhist attribute administrators in disruptive innovation society such as explicit, teamwork and participation, information technology and communication, intelligent, and best environmental development. 2. The developed model of Buddhist attribute administrators in disruptive innovation society for educational institutes has shown important factors and causal relationships, and the results that will lead to Buddhist attribute administrators in disruptive innovation society consisting of 1) attribute administrators in disruptive society, 2) attribute administrators in disruptive innovation, 3) Buddhist attribute administrators. Results of the investigation revealed that there were possible, accurate and appropriate. 3. The causal model for Buddhist attribute administrators in disruptive innovation society for educational institutes was proposed as a causal relationship model that fit with the empirical data (Chi-square = 72.53, df = 56, p = .068, GFI = .982, AGFI = .946, RMR = .026). Accounting for the variations in Buddhist attribute administrators in disruptive innovation society was 95.50 percent, and it indicated that attribute administrators in disruptive society, attribute administrators in disruptive innovation, and Buddhist attribute administrators can promote Buddhist attribute administrators in disruptive innovation society by having Buddhist attribute administrators as a mediator in the causal model for Buddhist attribute administrators in disruptive innovation society for educational institutes, and BIRD Model was proposed as knowledge from research.